Pengaruh Metode Pembelajaran Berbasis Proyek Terhadap Kemampuan Komunikasi dan Keterampilan Berpikir Kritis Peserta Didik di SMKN 5 Sidenrang Rappang - Diana; Muhammad Arsyad; H. Husain (Jurnal Ragam Pengabdian, 2026)
This study aimed to analyze the effect of Project-Based Learning (PjBL) on students’ critical thinking and communication skills at SMK Negeri 5 Sidenreng Rappang. A quantitative approach with a quasi-experimental posttest-only control group design was employed. The participants consisted of 65 tenth-grade students selected through simple random sampling. The experimental group was taught using PjBL, while the control group received Problem-Based Learning (PBL). Data were collected through a critical thinking skills test, communication skills observation sheets, and documentation. The data were analyzed using descriptive statistics, independent sample t-tests, and two-way ANOVA. The findings revealed that students in the PjBL group achieved a higher mean score in critical thinking (M = 24.85) than those in the PBL group (M = 21.91). Independent sample t-tests indicated significant differences in critical thinking skills between the two learning models among students with high communication skills (p = 0.019) and low communication skills (p = 0.001). Furthermore, the two-way ANOVA demonstrated a significant interaction between the learning model and communication skills on students’ critical thinking skills (p = 0.047). These findings suggest that Project-Based Learning is more effective than Problem-Based Learning in improving students’ critical thinking while simultaneously supporting the development of communication skills in vocational education.